And in rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Prevention and management of herbicide resistant weeds in rice: experiences from Central America with Echinochloa colona By B E Valverde, C R Riches & J C Caseley, CATIE, Costa Rica, NRI and the Institute of Arable Crops Research, UK, 2000. 126 pp. ISBN